Metabolite profiling of Bruguiera cylindrica reveals presence of potential bioactive compounds - Dahibhate, Nilesh Lakshman; Kumar, Kundan (PeerJ Analytical Chemistry, 2022)
Bruguiera cylindrica parts are commonly used in Chinese and Indian traditional medicine to treat diarrhea, fever, and many ailments. The present study aims non targeted analysis of key secondary metabolites of B. cylindrica by gas chromatography mass spectrometry (GC-MS) and ultra-high performance liquid chromatography hybrid quadrupole-Exactive-Orbitrap high resolution mass spectrometry (UHPLC-Q-Exactive Orbitrap HRMS). GC-MS and UHPLC-Q-Exactive Orbitrap HRMS were utilized for metabolic profiling of ethyl acetate extract of B. cylindrica leaves. Key metabolites in the extract were identified and predicted based on chemical similarity using online databases such as ChemSpider and mzCloud. Thirty-six compounds belonging to different classes of secondary metabolites viz. flavonoids, fatty acids, fatty acid amides, carboxylic acids, and alkaloids were identified in the extract. Pentacyclic triterpenes like betulin, ursolic acid and a tropine, an alkaloid with potential pharmacological and therapeutic activities such as anticancer properties, neuromuscular blockers and antioxidants, were also identified. This study combined GC-MS and UHPLC-Q-Exactive Orbitrap HRMS with available online database for effective and rapid identification of bioactive metabolites in the ethyl acetate extract of mangrove without individual standard application. This is the first report on the HRMS based secondary metabolic profiling of B. cylindrica, with comprehensive map of its biologically important metabolites.
Keywords: Mangrove; Bruguiera cylindrica; GC-MS; UHPLC-Q-Exactive Orbitrap HRMS